Model Mentoring Yesus dalam Injil Markus untuk Kepemimpinan Berkelanjutan di Gereja Lokal - Wennar, Wennar; Abraham, Jessica Elizabeth; Chandra, Tjahjadi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
Sustainable church leadership is a pressing challenge for many local congregations amid rapid social and technological changes. The core issue addressed in this study is the absence of a structured mentoring strategy for nurturing prospective spiritual leaders, resulting in stagnation within the church’s leadership pipeline. The purpose of this study is to develop a leadership mentoring model based on Jesus Christ’s discipleship pattern as depicted in the Gospel of Mark, providing a relevant and applicable framework for local church contexts. The study employs a Research and Development (R&D) approach combined with exegetical analysis of Mark 1:16–20, 3:13–19, 6:7–13, and 16:15–18. The data were collected through a systematic review of biblical texts, and analyzed exegetically to identify the key stages and dynamics of Jesus’ mentoring of the disciples. The results reveal four distinct phases of the mentoring process: a divine call, character formation, active ministry engagement, and commissioning for global mission. In conclusion, these findings form the basis for the LEAD (Locate, Empower, Act, Deploy) mentoring model, offering a structured and practical approach for local churches to cultivate spiritually mature leaders who are both mission-ready and capable of reproducing this discipleship process across generations.